Calcineurin inhibitors exacerbate coronary arteritis via the MyD88 signalling pathway in a murine model of Kawasaki disease. (21st July 2017) - Murata, K; Motomura, Y; Tanaka, T; Kanno, S; Yano, T; Onimaru, M; Shimoyama, A; Nishio, H; Sakai, Y; Oh-Hora, M; Hara, H; Fukase, K; et al.
Summary: Calcineurin inhibitors (CNIs) have been used off-label for the treatment of refractory Kawasaki disease (KD). However, it remains unknown whether CNIs show protective effects against the development of coronary artery lesions in KD patients. To investigate the effects of CNIs on coronary arteries and the mechanisms of their actions on coronary arteritis in a mouse model of KD, we performed experiments with FK565, a ligand of nucleotide-binding oligomerization domain-containing protein 1 (NOD1) in wild-type, severe combined immunodeficiency (SCID), caspase-associated recruitment domain 9 (CARD9) –/– and myeloid differentiation primary response gene 88 (MyD88) –/– mice. We also performed in-vitro studies with vascular and monocytic cells and vascular tissues. A histopathological analysis showed that both cyclosporin A and tacrolimus exacerbated the NOD1-mediated coronary arteritis in a dose-dependent manner. Cyclosporin A induced the exacerbation of coronary arteritis in mice only in high doses, while tacrolimus exacerbated it within the therapeutic range in humans. Similar effects were obtained in SCID and CARD9 –/– mice but not in MyD88 –/– mice. CNIs enhanced the expression of adhesion molecules by endothelial cells and the cytokine secretion by monocytic cells in our KD model. These data indicated that both vascular and monocytic cells were involved in the exacerbation of coronary arteritis. Activation of MyD88-dependent inflammatory signals in both vascular cells and macrophages appears to contribute to their adverse effects. Particular attention should be paid to the development of coronary artery lesions when using CNIs to treat refractory KD. Graphical Abstract: